US - Azerbaijan Relations in Caspian region (90s of the XX century) - E. A. Markova (Проблемы постсоветского пространства)
The collapse of the USSR resulted for Azerbaijan to pursue an independent foreign policy. Azerbaijan focused on establishing and furthering relations with Western states, primarily, with the United States. Official Baku considered the United States as an important partner to provide support for the economic development and production of hydrocarbon resources. On the other side, the United States also increased its focus on Azerbaijan due to the favorable geographical position of the Caspian state and the pro-Western attitude of its political elite. The US counted on taking advantage of Azerbaijan to change the flow of oil, which was supposed to be produced in the future. The United States played a decisive role in expanding Azerbaijan's cooperation with Western oil companies, which headed for the shores of the Caspian Sea. As a result, the Azerbaijani-American cooperation in the 90s of the XX century led Baku to chose the western direction in exporting its hydrocarbon resources as the principal one. In addition, under the US influence, Azerbaijan took a tough position on the international legal status of the Caspian Sea. Cooperation between the United States and Azerbaijan has had a great impact on the situation in the region, relations with Russia and the other Caspian states.